Effect of fungicides on Penicillium rot and quality of chilgoza seed - P.V. YADAV, R.C. SHARMA and (Indian Phytopathology, 2002)
Five fungicides were evaluated for the control of postharvest spoilage of Pinus gerardiana seeds caused by Penicillium citrinum. Fungal infection caused quantitative and qualitative seed damage. A carbendazim dip at 750 p.p.m. for 10 minutes was the most effective treatment for reducing seed spoilage. Oil content was max. in carbendazim-treated seeds followed by thiophanate-methyl treatment. Total proteins were highest after carbendazim and thiophanate-methyl treatments.